Rat epididymal sperm quantity, quality, and transit time after guanethidine-induced sympathectomy - Kempinas, W. D.; Suarez, J. D.; Roberts, N. L.; Strader, L.; Ferrell, J.; Goldman, J. M.; Klinefelter, G. R. (Soc Study Reproduction, 1998)
Guanethidine, a chemical that selectively abolishes peripheral noradrenergic nerves, was used to investigate the role of sympathetic innervation in the maintenance of epididymal sperm quantity and quality. Four groups of 10 adult male rats each were treated daily for 21 days, by i.p. injections, with either 0 (saline vehicle), 6.25, 12.5, or 25 mg/kg guanethidine. Norepinephrine content was reduced to undetectable levels in the cauda epididymidis in all guanethidine groups after 3 wk of treatment and was reduced to 7.4% of the control values after 1 wk of 6.25 mg/kg treatment. While body weight gain was significantly decreased at 12.5 and 25 mg/kg compared to that in controls, there was a significant increase in the weights of the seminal vesicles/coagulating glands in all treated groups. The number of homogenization-resistant spermatids per testis and the daily sperm production per testis remained unchanged. The weight of the epididymis was significantly increased at 6.25 and 12.5 mg/kg. Moreover, the number of cauda epididymal sperm and the transit time were increased significantly at 6.25 mg/kg (10.2 days) compared to values in the control cauda (6.3 days). Neither serum testosterone levels nor LH was affected in a dosage-related manner. There were no effects of guanethidine treatment on cauda epididymal sperm motility or morphology. A quantitative analysis of detergent-extracted cauda epididymal sperm proteins by SDS-PAGE revealed no differences, but there were diminutions in seven proteins in homogenates of caput/ corpus tissue. Histologic analysis of testis and epididymis sections revealed no differences between control and denervated animals. In a subsequent experiment the lowest effective dosage (6.25 mg/kg) was given to rats for 1 wk, and an increased number of cauda epididymal sperm and a delay in sperm transit were observed. Our results indicate that low-dosage guanethidine exposure denervates the epididymis within 1 wk, thereby delaying epididymal transit; however, neither 1- nor 3-wk exposure produces qualitative changes in the sperm.